Cytoplasmic Mislocalization of POU3F4 Due to Novel Mutations Leads to Deafness in Humans and Mice. Issue 8 (8th May 2013) - Parzefall, Thomas; Shivatzki, Shaked; Lenz, Danielle R.; Rathkolb, Birgit; Ushakov, Kathy; Karfunkel, Daphne; Shapira, Yisgav; Wolf, Michael; Mohr, Manuela; Wolf, Eckhard; Sabrautzki, Sibylle; de Angelis, Martin Hrabé; et al.
<x xml:space="preserve">Abstract</x> DFNX2 (OMIM #304400) is the result of mutations in the POU3F4 (POU domain class 3, transcription factor 4, BRN‐4) transcription factor that belongs to subclass III of the POU superfamily. Targeted capture and massively parallel sequencing was used to detect a human POU4F3 mutation, demonstrating the strength of this approach for diagnosis with only one affected individual . A second human mutation leads to a frameshift and a replacement of the normal C‐terminal end of the protein with a new segment. A Pou3f4 mutation predicted to lead to a stop codon results in deafness in an ENU‐derived mutant mouse. The human and mouse mutations complement one another and help define the molecular mechanisms associated with POU3F4 hereditary hearing loss in humans. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>